PENGARUH KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SABUN CAIR LIFEBUOY DI UD. ANIS BERKAT TELUKDALAM - Manao, Kornelia Wirnayanti (PARETO : Jurnal Riset Bisnis dan Manajemen, 2024)
This study aims to determine whether product quality affect the purchase decision of Lifebuoy liquid soap at UD. Anis Berkat Telukdalam. UD. Anis Berkat Telukdalam is located on Jalan Kueni number 12, Pasar Telukdalam sub-district, UD’s location is very strategic and easy to reach for consumers. The population in this study were all consumers who made purchases at Ud. Anis Berkat Telukdalam and The sample in this study was Lifebuoy liquid soap consumers at UD. Anis Berkat Telukdalam as many as 50 respondents were determined through a non-probability sampling method with incidental sampling techniques. The data used in this study is primary data, using questionnaires as research instruments. The results of this study show that the product quality variable (X) has a positive and significant effect on purchasing decisions (Y).